POLA JARINGAN PENDIDIKAN ISLAM SYEKH ALI IMRAN HASAN DALAM PEMBELAJARAN KITAB KUNING - Rahman, Abdul; Duski Samad; Misra; Rahmat (Institut Agama Islam Hamzanwadi NW Lombok Timur, 2025)
Nurul Yaqin Ringan-Ringan Islamic boarding school continues to develop as an educational institution that steadfastly maintains the quality of disciplines derived from the Kitab Kuning, which is inseparable from the Islamic education network of Sheikh Ali Imran Hasan. This research aims to examine the extent of the implementation of the Islamic education network model of Sheikh Ali Imran Hasan in the Kitab Kuning learning at Nurul Yaqin Ringan-Ringan Islamic boarding school. This research is a field study of a descriptive qualitative nature, located at the Nurul Yaqin Ringan-Ringan Islamic boarding school. The research informants include the Head of the Boarding School, the Head of the Foundation, Teachers, and Students. For data collection, the author used techniques and tools such as interviews, observations, and documentation. The result of this research is the existence of the Islamic education network pattern of Sheikh Ali Imran Hasan in the Kitab Kuning learning at Nurul Yaqin Ringan-Ringan Islamic boarding school, which can be seen from the aspects of learning components such as: objectives, materials, methods, media, evaluation, students, and educators.